2010
DOI: 10.2478/v10096-010-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-, and isotope stratigraphy around the Jurassic/Cretaceous boundary in the Vysoká Unit (Malé Karpaty Mountains, Slovakia): correlations and tectonic implications

Abstract: Magneto-and isotope stratigraphic studies in the Vysoká Nappe (Hlboča section, Fatric Unit, Malé Karpaty Mts, Slovakia) were performed. A generally decreasing δ 13 C isotope curve is interpreted as a primary trend from the Late Oxfordian (3.3 ‰ V-PDB) to the Late Tithonian (1.8-1.4 ‰ V-PDB). Data from the Tithonian part of the Tegernsee Formation probably reflect "local" basin processes connected with the breccia formation in the latest Tithonian/earliest Berriasian and/or with possible diagenetic overprint. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
3
36
0
2
Order By: Relevance
“…Increasingly negative δ 18 O values are often correlated with elevated temperatures in environmental settings where continental ice volume is at a minimum and evaporation or freshwater inputs are minor factors. Similar trends have been observed elsewhere (e.g., Tremolada et al, 2006;Price and Rogov, 2009;Grabowski et al, 2010b), but not universally as other studies found opposite trends (e.g., Emmanuel and Renard, 1993;Padden et al, 2002). Larger datasets through the Late Jurassic and into the Cretaceous, based on the isotopic composition of fossil belemnites and brachiopods (e.g., Veizer, et al, 1999;Gröcke et al, 2003;Wierzbowski, 2004;McArthur et al, 2007;Riboulleau et al, 1998;Bodin et al, 2009Bodin et al, , 2015Price and Rogov 2009;Dera et al, 2011;Alberti et al, 2012;Price et al, 2000;2013;Meissner et al, 2015), also show a similar trends (Fig.…”
Section: Oxygen Isotopes and Palaeoenvironmental Changesupporting
confidence: 78%
“…Increasingly negative δ 18 O values are often correlated with elevated temperatures in environmental settings where continental ice volume is at a minimum and evaporation or freshwater inputs are minor factors. Similar trends have been observed elsewhere (e.g., Tremolada et al, 2006;Price and Rogov, 2009;Grabowski et al, 2010b), but not universally as other studies found opposite trends (e.g., Emmanuel and Renard, 1993;Padden et al, 2002). Larger datasets through the Late Jurassic and into the Cretaceous, based on the isotopic composition of fossil belemnites and brachiopods (e.g., Veizer, et al, 1999;Gröcke et al, 2003;Wierzbowski, 2004;McArthur et al, 2007;Riboulleau et al, 1998;Bodin et al, 2009Bodin et al, , 2015Price and Rogov 2009;Dera et al, 2011;Alberti et al, 2012;Price et al, 2000;2013;Meissner et al, 2015), also show a similar trends (Fig.…”
Section: Oxygen Isotopes and Palaeoenvironmental Changesupporting
confidence: 78%
“…Pre-or syn-thrusting paleomagnetic data from the Krížna Nappe were reported by Kruczyk et al (1992), Grabowski (1995Grabowski ( , 2000 and Grabowski et al (2009Grabowski et al ( , 2010. These data show a systematic variation from the west (Malé Karpaty Mts) to the east (Tatra Mts) -the western localities show Cretaceous paleodeclinations rotated counterclockwise (CCW) up to 70°, further east in the Strážovské vrchy and Malá Fatra Mts this CCW rotation decreases to 60-25°, in the Nízke Tatry Mts it is only 20°, then no rotation was detected in the Chočské vrchy and Western Tatra Mts, while the easternmost sites in the Eastern Tatra Mts and the Ružbachy "island" have already shown a clockwise (CW) rotation 20-50°.…”
Section: Displacement Gradient and Displacement Trajectorymentioning
confidence: 79%
“…This fanwise arrangement of paleomagnetic declinations remains preserved also after subtracting the Late Tertiary CCW rotation of the whole Western Carpathian orogenic system by some 80° ( Grabowski & Nemčok 1999;Márton et al 1999;Grabowski 2010). Although particular directions might have been affected also by local tectonic phenomena, such as the vertical axis block rotation within wrench fault zones, or slight relative rotations of individual "core mountains" (Hrouda et al 2002), the fanwise pattern of paleomagnetic directions might be interpreted in terms of oroclinal bending (Kruczyk et al 1992;Grabowski 2010). Since the paleodeclinations are also subparallel to the presumed transport directions of the Krížna Nappe deduced from the kinematic criteria (Prokešová 1994;Kováč & Bendík 2002;Plašienka 2003), it is highly probable that they are also roughly parallel to the translation pathways of the Krížna Nappe System.…”
Section: Displacement Gradient and Displacement Trajectorymentioning
confidence: 81%
See 1 more Smart Citation
“…The three sec tors in the Up per Kimmeridgian-Lower Tithonian in ter val of the d 13 C curve might be iden ti fied also in the Hlboèa sec tion (Grabowski et al, 2010). Biostratigraphic cor re la tion of the sec tors fits quite well to the Ma³y Giewont and D³uga Val ley sec tions (Fig.…”
Section: Correlation Of the D 13 C Curve From The Ma£y Giewont Sectiomentioning
confidence: 60%